Aurantii Fructus extract alleviates DSS-induced colitis in mice via regulating NF-κB and Nrf2/HO-1 signaling pathways and modulating intestinal microbiota - Yu, JunBao; Mei, WenYa; Zhu, JiaYuan; Wang, ZhiHui; Liu, XiaoRong; Zhou, RiBao; Liu, XiangDan (Frontiers in Nutrition, 2025)
BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel disease characterized by progressive loss of intestinal function, highlighting an urgent need for effective therapeutics. This study aimed to investigate the protective effects of Aurantii Fructus extract (AFE) on dextran sulfate sodium (DSS)-induced UC in mice and its impact on the gut microbiota.MethodsThe chemical components of AFE were identified using high-performance liquid chromatography (HPLC). A murine model of DSS-induced colitis was established, and the therapeutic efficacy of AFE was assessed through the disease activity index (DAI), colon length measurement, and histopathological examination. Inflammatory status and oxidative stress markers were evaluated by enzyme-linked immunosorbent assay (ELISA) and western blotting, while the expression of tight junction proteins was analyzed via immunohistochemistry. Additionally, cecal contents were subjected to 16S rRNA gene sequencing to analyze changes in the intestinal microbiota.ResultsAFE treatment significantly alleviated the severity of colitis, as evidenced by reduced DAI scores, attenuated colon shortening, and improved histopathological damage. It restored the expression of the tight junction protein ZO-1 in the colon. AFE also markedly reduced the levels of pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) and suppressed the activation of the NF-κB pathway. Concurrently, AFE enhanced antioxidant capacity by increasing glutathione (GSH) levels, decreasing malondialdehyde (MDA), and activating the Nrf2/HO-1 signaling pathway. Furthermore, AFE treatment inhibited the proliferation of pathogenic bacteria and restored the homeostasis of the gut microbiota.ConclusionThe findings demonstrate that AFE confers a protective effect against DSS-induced UC. The underlying mechanism is associated with the inhibition of the NF-κB pathway, activation of the Nrf2/HO-1 antioxidant pathway, enhancement of the intestinal barrier, and restoration of gut microbiota homeostasis.